1999
DOI: 10.1002/1099-081x(199912)20:9<429::aid-bdd209>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ezlopitant, a novel non-peptidic neurokinin-1 receptor antagonist in preclinical species and metabolite kinetics of the pharmacologically active metabolites

Abstract: The pharmacokinetics of ezlopitant were determined in the rat, gerbil, guinea pig, ferret, dog and monkey after intravenous and oral administration. In general, ezlopitant is marked by high clearance values that approach or exceed hepatic blood flow values, moderate to high values for steady-state volume of distribution (3. 9-28 L/kg), and terminal phase half-life values ranging from 0.6 h in the guinea pig to 7.7 h in the rat. Oral bioavailability ranged from <0.2% (guinea pig) to 28% (dog). Data from portal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
(2 reference statements)
1
9
0
Order By: Relevance
“…To further elucidate the role of the NK1-receptor system in the regulation of consumption of natural reinforcers and ethanol, we evaluated the efficacy of a clinically safe and selective NK1-receptor antagonist, ezlopitant (CJ-11,974) [38], [39] to decrease sucrose and ethanol consumption and seeking. Ezlopitant has previously been investigated in clinical trials as a potential therapy for pain, chemotherapy-induced emesis and irritable bowel syndrome [40], [41]. The present study gives further support to the hypothesis that the NK1-receptor system might be a novel therapeutic target for addictive disorders.…”
Section: Introductionsupporting
confidence: 82%
“…To further elucidate the role of the NK1-receptor system in the regulation of consumption of natural reinforcers and ethanol, we evaluated the efficacy of a clinically safe and selective NK1-receptor antagonist, ezlopitant (CJ-11,974) [38], [39] to decrease sucrose and ethanol consumption and seeking. Ezlopitant has previously been investigated in clinical trials as a potential therapy for pain, chemotherapy-induced emesis and irritable bowel syndrome [40], [41]. The present study gives further support to the hypothesis that the NK1-receptor system might be a novel therapeutic target for addictive disorders.…”
Section: Introductionsupporting
confidence: 82%
“…Serum and Brain Tissue Binding Studies. The binding of CP-615,003 and CP-900,725 in pooled rat or dog serum (at 20 -2000 ng/ml CP-615,003 and 10 -1000 ng/ml CP-900,725), ex vivo protein binding samples from the clinical study, and 20% rat brain homogenate (100 ng/ml CP-615,003 or CP-900,725) prepared in Dulbecco's phosphate-buffered saline (pH 7.4) were determined by equilibrium dialysis as described previously (Reed-Hagen et al, 1999). Bioanalysis of CP-615,003 and CP-900,725 in dialysate and retentate samples was performed using the LC/MS/MS method described later.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetics of ezlopitant in several animal species have been reported and characterized by high clearance values with a moderate to high volume of distribution, a low to moderate terminal half-life, and low bioavailability (Reed-Hagen et al, 1999 …”
Section: Introductionmentioning
confidence: 99%
“…It also inhibited SP-induced contraction of guinea pig trachea with a pA 2 value of 7.8, but had no effects on the baseline tension and maximum contractile response. Recent clinical studies have shown that ezlopitant is effective for the treatment of either the acute or delayed phase of emesis associated with antineoplastic treatment using cisplatin, suggesting a role of NK1 receptor antagonists in the clinic for the control of emesis to improve the quality of life of cancer patients undergoing chemotherapy (Hesketh et al, 1999).The pharmacokinetics of ezlopitant in several animal species have been reported and characterized by high clearance values with a moderate to high volume of distribution, a low to moderate terminal half-life, and low bioavailability (Reed-Hagen et al, 1999 …”
mentioning
confidence: 99%
See 1 more Smart Citation